A case study of performance management system in a Malaysian government linked company - Mohd. Alwi, Norhayati; Abdul Khalid, Siti Nabiha (Emerald, 2009)
Purpose – The purpose of this paper is to explain the institutionalization process of the performance management system (PMS) in a Malaysian government-linked company (GLC). The study specifically looks at the changes brought by the GLC transformation programme introduced by the government.